Developing a Model of the Influence of Organizational Culture on Employee Performance and Job Satisfaction at PT. XYZ with PLS-SEM Method - Areta Shafa Ardelia; Renny Rochani; Retno Wulan Damayanti (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2024)
In the era of industrial development, the urgency of the human resource factor is undeniable, because humans are the core elements that run the industry. In an organization, because of the process of interaction between individuals, there must be a culture that grows and becomes the basis for the behavior of the organization. The problem that occurred at PT. XYZ is that there is still a lack of optimization of the management of the company's organizational culture. Therefore, this study focuses on how to achieve optimal organizational culture management, mapped with a model of the influence of organizational culture on employee performance and job satisfaction. The method used in this research is descriptive method supported by a quantitative approach. Data collection was carried out through interviews and questionnaires on the sample population of employees working at PT. XYZ with random sampling method and Slovin formula. The data were processed and analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results of the research show that organizational culture has a significant influence on employee performance and job satisfaction at PT. XYZ.